2006
DOI: 10.1038/sj.onc.1210032
|View full text |Cite
|
Sign up to set email alerts
|

The role of the MKK6/p38 MAPK pathway in Wip1-dependent regulation of ErbB2-driven mammary gland tumorigenesis

Abstract: There is increasing evidence for the role of wild-type p53 induced phosphatase 1 (Wip1) phosphatase in the regulation of tumorigenesis. To evaluate Wip1 as a breast cancer oncogene, we generated a mouse strain with targeted expression of Wip1 to the breast epithelium. We found that these mice are prone to cancer when intercrossed with transgenics expressing the ErbB2 oncogene but not conditional knockouts for Brca2. This tumor-prone phenotype of Wip1 is fully eliminated through attenuation of proliferation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 18 publications
5
81
0
Order By: Relevance
“…This observation has led to the hypotheses that PPM1D overexpression is a causative factor in tumorigenesis and that inhibition of PPM1D may be of therapeutic benefit. However, validation of PPM1D as a therapeutic target in cancer has focused on the reduction of normal Ppm1d levels in the mouse using gene targeting (Bulavin et al, 2004;Nannenga et al, 2006) or, in one instance, transgenic overexpression of PPM1D in the mouse breast epithelium (Demidov et al, 2007). The proposed model of PPM1D involvement in cancer involves overexpression in human tissue and, therefore, an important proof-of-principle experiment is to show that inhibition of aberrantly elevated, but not basal, levels of PPM1D can be selectively lethal in human tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…This observation has led to the hypotheses that PPM1D overexpression is a causative factor in tumorigenesis and that inhibition of PPM1D may be of therapeutic benefit. However, validation of PPM1D as a therapeutic target in cancer has focused on the reduction of normal Ppm1d levels in the mouse using gene targeting (Bulavin et al, 2004;Nannenga et al, 2006) or, in one instance, transgenic overexpression of PPM1D in the mouse breast epithelium (Demidov et al, 2007). The proposed model of PPM1D involvement in cancer involves overexpression in human tissue and, therefore, an important proof-of-principle experiment is to show that inhibition of aberrantly elevated, but not basal, levels of PPM1D can be selectively lethal in human tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…INK4a levels are increased and the mice are protected from the early onset of mammary tumors in response to Ras, Neu and ErbB2 oncogenes Demidov et al, 2006). The addition of a pharmacological inhibitor of p38 activity to the Wip1-null mice reduced p16…”
Section: Role Of P38 In Cancermentioning
confidence: 99%
“…INK4a expression and led to the formation of mammary tumors , whereas mice bearing a constitutively active form of the p38 activator MKK6 suppressed the tumor-prone phenotype of mice overexpressing Wip1 in mammary epithelium (Demidov et al, 2006).…”
Section: Role Of P38 In Cancermentioning
confidence: 99%
“…105,[107][108][109][110] Overexpression experiments have shown that Wip1 induces malignant transformation in collaboration with other oncogenes, protects against oncogene-induced premature senescence and apoptosis, and accelerates tumorigenesis in vivo. 106,107,123,124 Conversely, Ppm1d-null MEFs and mice are resistant to oncogene-induced transformation and to spontaneous and oncogene-driven tumorigenesis, respectively. 119,122,123 Although most of the oncogenic properties of Wip1 are ascribed to its ability to suppress the p53 pathway and the DNA damage response, concomitant inhibition of pRb tumor suppressor activity because of transcriptional repression of p16 INK4a expression may also play a role.…”
Section: Deregulation Of the P14 Arf -Mdm2-p53 Axis By Ppm1d (Wip1)mentioning
confidence: 99%